Sanguineous normothermic machine perfusion improves hemodynamics and biliary epithelial regeneration in donation after cardiac death porcine livers. Issue 8 (2nd July 2014) - Liu, Qiang; Nassar, Ahmed; Farias, Kevin; Buccini, Laura; Baldwin, William; Mangino, Martin; Bennett, Ana; O'Rourke, Colin; Okamoto, Toshiro; Uso, Teresa Diago; Fung, John; Abu‐Elmagd, Kareem; et al.
<x xml:space="preserve">Abstract</x> The effects of normothermic machine perfusion (NMP) on the postreperfusion hemodynamics and extrahepatic biliary duct histology of donation after cardiac death (DCD) livers after transplantation have not been addressed thoroughly and represent the objective of this study. Ten livers (5 per group) with 60 minutes of warm ischemia were preserved via cold storage (CS) or sanguineous NMP for 10 hours, and then they were reperfused for 24 hours with whole blood in an isolated perfusion system to simulate transplantation. In our experiment, the arterial and portal vein flows were stable in the NMP group during the entire reperfusion simulation, whereas they decreased dramatically in the CS group after 16 hours of reperfusion (P < 0.05); these findings were consistent with severe parenchymal injury. Similarly, significant differences existed between the CS and NMP groups with respect to the release of hepatocellular enzymes, the volume of bile produced, and the levels of enzymes released into bile (P < 0.05). According to histology, CS livers presented with diffuse hepatocyte congestion, necrosis, intraparenchymal hemorrhaging, denudated biliary epithelium, and submucosal bile duct necrosis, whereas NMP livers showed very mild injury to the liver parenchyma and biliary architecture. Most importantly, Ki‐67 staining in extrahepatic bile ducts showed biliary epithelial regeneration. In conclusion, our findings advance the knowledge of the postreperfusion events that characterize DCD livers and suggest NMP as a beneficial preservation modality that is able to improve biliary regeneration after a major ischemic event and may prevent the development of ischemic cholangiopathy in the setting of clinical transplantation. Liver Transpl 20:987–999, 2014. © 2014 AASLD.